2010
DOI: 10.1111/j.1365-2966.2010.17026.x
|View full text |Cite
|
Sign up to set email alerts
|

Primordial density perturbations with running spectral index: impact on non-linear cosmic structures

Abstract: We explore the statistical properties of non-linear cosmic structures in a flat cold dark matter ( CDM) cosmology in which the index n S of the primordial power spectrum for scalar perturbations is allowed to depend on the scale. Within the inflationary paradigm, the running of the scalar spectral index can be related to the properties of the inflation potential, and it is hence of critical importance to test it with all kinds of observations, which cover the linear and non-linear regime of gravitational insta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 114 publications
3
8
0
Order By: Relevance
“…Whereas at the low-mass end (M 2 × 10 13 M ), the negative running cosmologies tend to predict slightly lower concentrations, the effect on these scales is small compared to the high-mass end. A similar result was found by Fedeli et al (2010), who predicted low-mass halos to have a lower concentration value in a negative running cosmology, but high-mass halos to have a slightly higher concentration.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Whereas at the low-mass end (M 2 × 10 13 M ), the negative running cosmologies tend to predict slightly lower concentrations, the effect on these scales is small compared to the high-mass end. A similar result was found by Fedeli et al (2010), who predicted low-mass halos to have a lower concentration value in a negative running cosmology, but high-mass halos to have a slightly higher concentration.…”
Section: Discussionsupporting
confidence: 86%
“…This makes sense when looking at the HMF, or the comoving halo space density, which showed that a negative running cosmology led to an increase in the number of halos in this higher mass bin, and therefore one can expect them to be a less biased tracer of the underlying matter distribution, which as a result will lead to a lower clustering signal compared to the no-running cosmology's result. This result agrees with that predicted by Fedeli et al (2010), who showed that in a negative running cosmology dark matter halos in the cluster regime are less biased compared with the standard model (see figure 10 in Fedeli et al 2010). The other two negative running cosmologies see a similar trend, but not to the same level.…”
Section: Clustering Of Halossupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, these effects can also alter the dark matter profile within individual halos and hence the gas profile as well, potentially affecting the 21 cm absorption sig- nal. Consequences for the halo dark matter profile of massive neutrinos [60], RSI [61] and WDM [8,62] have been studied to some extent for galaxy-to cluster-scale halos at low redshifts, indicating that they are affected mainly in the central regions with r/r vir 0.1. Although no corresponding work exists for high-redshift minihalos, we may speculate that the impact is less than that due to the mass function with regard to our results, for which the outer regions of the halo are more relevant (Fig.2).…”
Section: Discussion and Summarymentioning
confidence: 99%